2020
DOI: 10.1021/acscatal.0c02050
|View full text |Cite
|
Sign up to set email alerts
|

Methane Combustion over Pd/Al2O3 Catalysts in the Presence of Water: Effects of Pd Particle Size and Alumina Crystalline Phase

Abstract: The effects of the Pd particle size and the Al2O3 crystalline phase of Pd/Al2O3 catalysts on the CH4 combustion in the presence of H2O were investigated. According to X-ray absorption fine structure (XAFS) measurements, it was revealed that, during the CH4 combustion, the Pd nanoparticles existed on the Al2O3 support as a PdO phase, while the crystallinity of PdO depended on the Pd particle size. On the basis of X-ray diffraction (XRD), amorphous PdO particles with a size of <7 nm exhibited low activity for CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(99 citation statements)
references
References 43 publications
12
87
0
Order By: Relevance
“…Chen et al found a decrease in activity with an increase in the Pd particle size [18]. The increase in catalytic activity with particle size was reported by Stakheev et al [24] and Murata et al [25].…”
Section: Introductionmentioning
confidence: 71%
“…Chen et al found a decrease in activity with an increase in the Pd particle size [18]. The increase in catalytic activity with particle size was reported by Stakheev et al [24] and Murata et al [25].…”
Section: Introductionmentioning
confidence: 71%
“…However, Murata et al. reported that the Pd nano‐particles over the bare γ−Al 2 O 3 exposed an amorphous‐like surface with a high fraction of corner sites, resulting in low activities and hydrothermal durability for lean methane combustion [6] . Thus, improving the potential of γ−Al 2 O 3 supported nano‐catalysts requires a meticulous analysis of the effects of active dopants at the atomic scale on the formation of active Pd sites through electronic and steric interactions.…”
Section: Methodsmentioning
confidence: 99%
“…For decades, a lot of efforts have been put into development of palladium catalysts for lean CH 4 oxidation, finding that the activity of the CH 4 oxidation is closely related to the shape and size of Pd phase, and even with reaction gas compositions. [5] Besides, numerous research studies have been devoted to unravel the chemical nature for the remarkable activity of Pd species, whereas there are still some controversies in reported literature concerning which is the most active state of the Pd-based catalysts, and the nature and identity of the active phase in Pd catalysts also remain a subject of active dispute. [6] Notably, it is generally reported that metallic Pd, [7] PdO, [8] reduced PdO x [9] and the synergy among disparate species [10] have been supposed as the possible active phase for methane oxidation.…”
Section: Introductionmentioning
confidence: 99%